Risk factors for stoma outlet obstruction: systematic review and meta-analysis - Ali Toffaha (18111886) (2025)
Introduction Stoma outlet obstruction (SOO) is a serious postoperative complication that can lead to significant morbidity, including prolonged hospitalization, increased healthcare costs, and reduced quality of life. This study, the first systematic review and meta-analysis on SOO, aims to identify and analyze key risk factors of SOO, calculate its pooled incidence, and systematically review its diagnostic features, clinical symptoms, imaging modalities, management strategies, prognosis, and associated outcomes. Methods This systematic review and meta-analysis followed PRISMA 2020 guidelines and included 16 retrospective cohort studies, identified through a comprehensive search of multiple databases, with data on risk factors for SOO. The study analyzed four key variables reported by three or more studies, assessed study quality using the MASTER scale, and synthesized findings using the quality effects model to evaluate heterogeneity and publication bias. Results This study included 16 retrospective cohort studies involving 2,228 patients, of whom 362 developed SOO. Increased rectus abdominis muscle thickness was found to significantly increase the risk of SOO (odds ratio [OR] 4.04, 95% confidence interval [CI] 2.36–6.93). High output stoma was another associated risk factor (OR 4.16, 95% CI 2.03–8.51). The type of ileostomy also played a critical role, with loop ileostomy showing a significantly higher risk of SOO compared to end ileostomy (OR 6.53, 95% CI 2.83–15.03). Although age was assessed as a potential risk factor, it did not show a statistically significant association with SOO (OR 1.69, 95% CI 0.44–6.54). Conclusion This systematic review and meta-analysis identified significant risk factors for SOO, including increased rectus abdominis muscle thickness, high output stoma, loop ileostomy. We also reported other contributing factors, such as ileal pouch–anal anastomosis, shorter ileal pouch-to-ileostomy distance, oral inferior technique, smaller aperture size, higher BMI, and increased subcutaneous fat thickness. The findings emphasize the importance of tailored surgical techniques, such as stoma maturation using the oral superior technique, ensuring no twist at the mesentery, avoiding stoma limb angulation, creating the stoma slightly more proximally in cases of ileal pouch-anal anastomosis, and optimizing aperture size, along with vigilant postoperative care to reduce SOO incidence and improve patient outcomes. Other Information Published in: Langenbeck's Archives of Surgery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00423-025-03892-5